Business Ethics Education in Bahrain: Staff Perceptions - Ramadhan , Sayel; Miranda, Jennifer (International Journal of Psychosocial Rehabilitation, 2020)
Corporate scandals early in the twenty first century have directed to repeated calls for business ethics education. The main purpose of this study is to explore the perceptions of business faculty at universities in Bahrain regarding the importance, coverage, instructing techniques and barriers to business ethics education. A questionnaire survey was used to collect the data. Using descriptive statistics and the nonparametric Kruskal-Wallis test, the results show that business ethics education is important because it "encourages students to learn ethical values" and "develops sense of integrity and honesty on students". In addition, respondents perceive cases as the most important method to teach ethics and they did not perceive any significant barriers to teaching business ethics. Most respondents prefer to integrate ethics in all business courses. Finally, there were no significant differences between gender, age and ethical decision making behavior and gender and instructing techniques. Based on the findings, it is recommended that all colleges of business in Bahrain should include business ethics as a compulsory course for all business majors.